The spatial pattern of disasters in public schools in Ibadan, Nigeria (2015)
This research investigated the spatial pattern of public schools affected by disasters in Ibadan from 2009 to 2014. It also examined the occurrences and effects of disasters on educational facilities, the disaster preparedness facilities and users' knowledge of the facilities. Using the stratified random sampling technique, three urban out of five and two rural out of six local government areas (LGAs) in Ibadan were randomly selected for the study. All the 50 public schools affected by the 52 disaster events from 2009 to 2014 in the three urban and two rural LGAs, representing 87.7 per cent of the total number of public schools affected by disaster in Ibadan, were selected and geo-referenced. Copies of a questionnaire was administered to heads of schools and three teachers were randomly selected in each of the 50 schools, giving a total of 200 (19.4 per cent) of the total population. Staffs of Oyo State Ministry of Education, Oyo State Emergency Management Agency and Oyo State Universal Basic Education Board were interviewed. Informal interviews were also held with school prefects. Secondary data were obtained from published and unpublished sources. Descriptive and inferential statistics were used for data analysis. Between 2009 and 2014, 52 disaster events occurred and 50 public schools were affected. Sixty-eight (68) school buildings were affected and one life was lost. The public schools affected increased from six (6) in 2010 to seventeen (17) in 2011 owing to the rainfall of26 August, 2011. About 42.0% of the schools located on steep terrain experienced gully erosion. Only 4.7% schools had fire extinguishers and 60.5% had first-aid kits. Roofs of school buildings were easily blown off by the rainstorm/windstorm. Nearest neighbor analysis revealed a random and a dispersed pattern of public schools affected by disaster in urban and rural areas, respectively. The study recommended that the Ministry of .. Education, in collaboration with Oyo State Emergency Management Agency and other relevant stakeholders in disaster management, should promote awareness about safe schools, develop vulnerability assessment guidelines for schools, and ensure, that every school has disaster contingency plan.